Ways of creativity formation of master students. (Journal of Educational Sciences, 2022)
Currently, creative, innovative, intellectual, creative individuals with formed professional competencies are in demand. In this regard, the postgraduate education system provides for the formation of new facets in future undergraduates, such as motivation, innovation, mobility, flexibility, dynamism and versatility, the upbringing of a creatively thinking, creative and creative personality.The aim of the research is to provide theoretical substantiation of the formation of future masters' creativity and presentation of its model in the process of postgraduate education. In this direction, it is envisaged that the system of training future masters at the university is aimed at mastering theoretical material, full understanding, free creative self-expression. The article presents the structure of creativity in accordance with the peculiarities of the formation of the creative activity of masters, the content, components, levels and criteria of their formation are determined, a model is developed. The methodological and theoretical foundations of the methodological positions are examined, on the philosophical pedestal, fundamental ideas about the essence of human cognitive activity of personality-oriented learning systems and psychological and pedagogical assistance in the formation of creativity in research, as well as concepts in the field of education are revealed. It is noted that its practical significance lies in the possibility of using higher and postgraduate education.Keywords: creativity, future masters, creativity of future masters, creativity, modeling